PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS (Studi kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2004 – 2014) - Muhammad Faisal (Soso-Q : Jurnal Manajemen, 2017)
This study has a purpose to determine the effect of cash turnover, receivables turnover, inventory turnover on profitability. Population in this research is manufacture company listed in Bursa Efek Indonesia as many as 15 companies sub sector of food and beverage industry and 6 sub industry sector cosmetics and household goods period of year 2004-2014. With Purposive Sampling technique, 10 samples were obtained. Data analysis technique used is ratio analysis and multiple linier regression analysis method, F test, and T test that is test of influence between independent variable and dependent variable. The main goal of the company is to maximize prosperity for its shareholders. One way to achieve that goal is to increase the profitability of the company. All company resources must be driven to gain profitability.The results of this study indicate that: 1) Cash turnover has a positive and significant impact on profitability; 2) Involvement Turnover has a positive and significant impact on profitability; 3) Inventory turnover has a positive and significant impact on profitability; 4) cash turnover, receivable turnover, and inventory turnover simultaneously have a positive and significant effect on profitability. Profitability shows the company's superiority in business competition. The higher the level of profitability then the company's performance the better.Keywords: cash turnover, receivable turnover, inventory turnover and profitability